Influence of the internal layer cracks on the cracking of flexural three-layer concrete members - Marčiukaitis, Gediminas; Juknevičius, Linas (Journal of Civil Engineering and Management, 2002)
Three-layer structures made of concrete-type materials usually have an internal layer of a less strength, which serves as thermal insulation and makes the structure more light. Therefore cracks may appear in the internal layer of a bended structure earlier than in the external tensile layer. This paper deals with an influence of cracks in the internal layer and its deformational properties on the calculation of layered structures made of concrete-type material. A model is presented for calculating flexural three-layer members for crack resistance taking into account the internal layer cracking. Analytical procedures are described for calculating the depth of the tensile zone and cracking of the internal layer. The paper also presents an analysis of the influence of deformational properties of the material (concrete) on the stress-strain relationship in the layers. Frist Published Online: 30 Jul 2012